2006
DOI: 10.1093/ilar.47.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Swine Models of Type 2 Diabetes Mellitus: Insulin Resistance, Glucose Tolerance, and Cardiovascular Complications

Abstract: In humans, diabetes mellitus (DM) is considered a heterogeneous metabolic disorder. Swine have been used as a model for many human conditions including type 1 (insulindeficient) and type 2 (insulin-resistant) DM research because of their phenotypic similarities to humans including: cardiovascular anatomy and function, metabolism, lipoprotein profile, size, tendency to obesity, and omnivorous habits. There is phenotypic overlap between the two types of DM and pig models show characteristics and complications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 93 publications
2
113
0
1
Order By: Relevance
“…These results suggested that Mstn might play roles as not only a regulator but also a paracrine factor, which is consistent with a previous study (Guernec et al, 2003). Furthermore, swine, especially Yorkshire pigs, are typically used as a model for type-1 or type-2 diabetes mellitus in previous studies (Suzuki et al, 2001;Natarajan et al, 2002;Bellinger et al, 2006). Guo et al (2012) found that inhibition of Mstn might be an effective treatment for diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…These results suggested that Mstn might play roles as not only a regulator but also a paracrine factor, which is consistent with a previous study (Guernec et al, 2003). Furthermore, swine, especially Yorkshire pigs, are typically used as a model for type-1 or type-2 diabetes mellitus in previous studies (Suzuki et al, 2001;Natarajan et al, 2002;Bellinger et al, 2006). Guo et al (2012) found that inhibition of Mstn might be an effective treatment for diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…More specialized metabolic investigations would study the mechanisms of aberrant insulin signalling during hormonal resistance using isotopic measurements of intracellular metabolic pathway fluxes in peripheral organs, such as liver and muscle. In addition, metabolic changes on the level of the regulation of glycolysis versus gluconeogenesis, citric acid cycle fluxes, sources of plasma glucose, nutrient oxidation and futile metabolic cycle fluxes also have to be taken into account if one wants to fully understand the phenotype of a new animal model of diabetes [50][51][52].…”
Section: Animal Model Proteomicsmentioning
confidence: 99%
“…Although rat preadipocytes and http://bmbreports.org BMB reports adipocytes lines are commonly used in obesity studies, it has been suggested that porcine preadipocytes are a better model for the study of obesity and its related disorders because porcine preadipocytes possess higher lipogenic capacity and similar lipogenic patterns to human adipocytes (21)(22)(23). Fernandez reported that guinea pigs could be used as models to study hepatic cholesterol and lipoprotein metabolism (24).…”
Section: Introductionmentioning
confidence: 99%